Preparation and Characterization of Ni-Doped Calcium Silicate Hydrate Based on Steel Slag: Adsorption Capacity for Rhodamine B from Aqueous Solution - Lu Zeng; Ligang Yang (Journal of Chemistry)
Calcium silicate hydrate based on steel slag (SCSH) and Ni-doped SCSH (NSCSH) were synthesized under specific hydrothermal conditions at saturated vapor pressure and 185°C for 7 hours. The structure and morphology of SCSH and NSCSH were characterized by XRD, SEM, and N2 adsorption/desorption. SCSH mainly consisted of amorphous calcium silicate hydrate gel (C-S-H gel) together with some flake-like tobermorite and NSCSH consisted of crystalline tobermorite and xonotlite. The addition of Ni(NO3)2 had great influence on microstructure of the composites, and SCSH possesses a mesoporous structure with slit-shaped pores, but NSCSH has narrow distributions of pore size. Furthermore, NSCSH has a higher adsorption capacity for Rhodamine B (RhB) than SCSH with removal percentages of RhB of about 52.4% and 88.2%, respectively. In addition, the effects of NSCSH dosage and pH values on the adsorption of RhB were investigated. Adsorption isotherm parameters are obtained from both Langmuir and Freundlich analysis and showed a better fit to a Langmuir model. All results indicated that NSCSH has a great potential to be a safe, easily-made, and cost-effective material for the control of RhB contamination.